The Impact of Financial Information, Non-Financial Information, and Macroeconomic Conditions on IPO Underpricing: Evidence from the Indonesia Stock Exchange - Yulfanis Aulia Masrifa, Andyni; Septiana, Era (Economic and Business Horizon, 2025)
This study aims to determine the effect of financial information, non-financial information, and macroeconomic conditions on the level of underpricing. The research variables used are financial information variables (Return on Assets and Debt to Equity Ratio), non-financial information variables (company size and company age), and macroeconomic conditions variables (inflation and interest rates). This study is a quantitative study using multiple linear regression analysis methods. The population of this study were companies conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange (IDX) in 2018-2022, totaling 273 companies and a sample size of 235 companies selected using the purposive sampling method. The results of the study showed several results, including (1) financial information variables (ROA and DER) did not affect the level of underpricing in companies conducting IPOs on the IDX in 2008-2022; (2) non-financial information variables show different results in their influence on the level of underpricing where company size influences the level of underpricing, while company age does not have a significant effect on the level of underpricing; (3) macroeconomic condition variables also show different results in their influence on the level of underpricing where inflation has no effect and interest rates influence underpricing.